2006
DOI: 10.1159/000097601
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Paediatric Renal Transplantation: Follow-Up of 300 Children from 1973 to 2000

Abstract: Background/Aim: To report our experience of paediatric renal transplantation at Great Ormond Street and Royal Free Hospitals since the inception of the programme. Methods: Retrospective review of the patient and transplant survival and influencing factors in the 300 children transplanted between 1973 and 2000. Results: 300 children had received a total of 354 transplants; 56 were living-related donations. The median age at transplantation was 10.3 (range 1.4–17.9) years. Forty-four percent had congenital struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 56 publications
8
63
1
Order By: Relevance
“…Furthermore, Najarian et al (22,27) found no difference in patient or graft survival between children aged Ͻ1, 1 to 2, and 2 to 5 yr. More recent analyses showed equivalent results in age groups Ͻ1, 1 to 4, and 5 to 13 yr (28). Rees et al (29) documented that the outcome of successful transplantation was unaffected by age at time of transplantation. The survival of living-related donor transplants was superior to deceased-donor transplants for the first 5 yr.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Najarian et al (22,27) found no difference in patient or graft survival between children aged Ͻ1, 1 to 2, and 2 to 5 yr. More recent analyses showed equivalent results in age groups Ͻ1, 1 to 4, and 5 to 13 yr (28). Rees et al (29) documented that the outcome of successful transplantation was unaffected by age at time of transplantation. The survival of living-related donor transplants was superior to deceased-donor transplants for the first 5 yr.…”
Section: Discussionmentioning
confidence: 99%
“…4 Very young recipient age was associated with poorer short-term graft survival, probably because of greater A B technical complexity and higher incidence of vascular thrombosis and acute cellular and vascular rejection in this group. 14 The 1-and 5-year graft survival for the present patients were comparable to reported outcomes from the Collaborative Transplant Study registry (Figure 2).…”
Section: Discussionmentioning
confidence: 92%
“…16 The frequency of living donation varies in different regions including North America (60%), United Kingdom (25%), and Germany (18%), possibly because of variation in cultural and social attitudes and features of donation in the transplant programs. 4,17,18 Donor nephrectomy was performed laparoscopically in 445 transplants (90%). Previous randomized and nonrandomized studies in adults showed that laparoscopic donor nephrectomy is associated with longer operative and warm ischemia times but lower duration of hospitalization and analgesic requirements than open nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that the degree of improvement in LV contractility after transplantation was a 56% increase in fractional shortening, and it was larger than that expected for correction of anemia [27]. Reduction of the LVMI after renal transplantation has not been a universal observation; more recent studies did not find significant change in LVMI following transplantation [28], and Mitsnefes et al [9] showed that there was no significant difference in the mean values for the LVMI in children and adolescents while on dialysis and after renal transplantation. Bullington et al reported in a cross-sectional study that LVH is a known cardiovascular risk factor that is frequent in children after kidney transplantation.…”
Section: Discussionmentioning
confidence: 98%